Comparison of Outcomes in Maternal Opiate Medical Support Using CenteringPregnancy Versus Maternity Care Home [24K]. (May 2016) - Adams, Jacquelyn H.; Liew, Zi-Qi; Sangtani, Ajleeta; Frantz, Karen; McCarroll, Michele L.; Silber, Angela
Abstract : INTRODUCTION: Opioid addiction in pregnancy is a public health crisis and efforts to improve fetal outcomes have taken many forms. METHODS: A retrospective matched case-control study of opiate addicted pregnant women was conducted to compare two prenatal visit models: 1. Group medical visit format using CenteringPregnancy® (CGC) or 2. Standard one-on-one Maternity Care Home medical visits (MCH). The CGC prenatal visits met weekly/biweekly in lieu of regular MCH prenatal visits. The MCH prenatal visits occurred based on the prenatal care plan. Outcomes of maternal age (MA), gestational age (GA), Neonatal Intensive Care Unit admission (NICU), APGAR 5-minute (APGAR-5), total number of prenatal visits (TPV), ultrasound visits including antenatal testing (USV), emergency room obstetrical triage visits (ERV), and breastfeeding at discharge (BF) were analyzed. RESULTS: The CGC and MCH groups were matched cohorts ( P =.938) in age: 27.8±3 years; race: 98% Caucasian; insurance type: 100% public; and marital status: married 15%, single 78%, divorced 3%. Statistically significant differences were noted in TPV: 17.4±6 versus 8.6±7 ( P <.001); USV: 6.7±4 versus 3.7±3 ( P <.003); and ERV: 1.8±2 versus 3.2±2 ( P <.02). No statistical significant differences were noted between CGC versus MCH matched cohorts in GA 75%, versus 69% full term ( P =0580); APGAR-5: 8.9±0.2, 8.5±1.6, ( P =.121); NICU: 12 versus 11 ( P =.795); and BF: 79% versus 64% ( P =.174), respectively. CONCLUSION: These results indicate that the CGC group prenatal visit model for opiate addicted pregnant women is clinically advantageous over MCH for ensuring prenatal visit compliance and reducing ERV in a high risk population.